2020
DOI: 10.1111/dom.14090
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide treatment in overweight and obese patients with type 1 diabetes: A 26‐week randomized controlled trial; mechanisms of weight loss

Abstract: Aim To investigate the effects of liraglutide treatment on glycaemic control and adipose tissue metabolism in overweight and obese people with type 1 diabetes (T1DM). Research design and methods A total of 84 adult overweight and obese patients with T1DM, with no detectable C‐peptide, were randomized (1:1) to either placebo or 1.8 mg/d liraglutide for 6 months. Blood samples were collected at 0, 12 and 26 weeks. Subcutaneous adipose tissue biopsies, a high‐calorie high‐fat meal challenge test, continuous gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
54
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 25 publications
3
54
4
1
Order By: Relevance
“…For these studies, the mean age of participants was 43.9 (SD 13.6) years, with a duration of diabetes of 21.5 (SD 12.5) years, body weight 83.2 (SD 16.7) kg and an HbA1c of 8.1% (SD 0.8%) (65.5 mmol/mol). Changes in body composition‐related measurements were reported in four studies 38–41 (S12 and S13). The ethnicity of participants was documented in most studies and mainly as Caucasian, with a few studies including black African Americans and Asians (Table S8).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For these studies, the mean age of participants was 43.9 (SD 13.6) years, with a duration of diabetes of 21.5 (SD 12.5) years, body weight 83.2 (SD 16.7) kg and an HbA1c of 8.1% (SD 0.8%) (65.5 mmol/mol). Changes in body composition‐related measurements were reported in four studies 38–41 (S12 and S13). The ethnicity of participants was documented in most studies and mainly as Caucasian, with a few studies including black African Americans and Asians (Table S8).…”
Section: Resultsmentioning
confidence: 99%
“…Out of 33 studies, 11 reported arterial blood pressure at baseline and postintervention 13,37,40,41,49,50,56,57,66–68 (Tables S23 and S24). Four of the 11 studies reported a significant decrease in either systolic or diastolic blood pressure or both from baseline for within groups and difference versus placebo 40,41,49,56 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations